Associations between glycan signature alterations and the cellular antigenic properties of passaged chondrocytes - Homan, Kentaro; Tokuhiro, Taiki; Onodera, Tomohiro; Hanamatsu, Hisatoshi; Furukawa, Jun-ichi; Ebata, Taku; Matsuoka, Masatake; Kadoya, Ken; Terkawi, M. Alaa; Iwasaki, Norimasa (Frontiers in Immunology, 2024)
BackgroundCartilage repair is a significant clinical challenge because of the limited intrinsic healing capacity. Current therapeutic strategies, such as cell transplantation therapy, aim to overcome this challenge by replacing damaged tissue with healthy cells. However, the long-term survival and functionality of transplanted cells remain major hurdles.ObjectiveThis study investigated the impact of chondrocyte passaging on glycan profiles and their antigenic properties. We hypothesized that alterations in glycan composition due to passaging may contribute to the enhanced ability to activate macrophages, thereby affecting the outcome of cell transplantation therapy.MethodsPeritoneal macrophages and primary articular chondrocytes were isolated from C57BL/6 mice to establish direct and indirect coculture models. Macrophage activation was assessed by measuring the concentrations of IL-6 and nitric oxide in the culture supernatants or their gene expression. Glycome analysis of various glycoconjugates was performed by glycoblotting methods combined with the SALSA procedure for N-glycans and GSLs and the BEP method for O-glycans.ResultsOur results revealed that direct coculture of macrophages with passaged chondrocytes increased the production of proinflammatory cytokines, including IL-6 and NO, as the number of passages increased. With increasing passage number, the expression of GD3 substantially decreased, and the expression of GM3, especially GD1a, significantly increased. Coculturing passaged GM3S knockout chondrocytes with macrophages significantly suppressed IL-6 expression, implying reduced macrophage activation.ConclusionThe observed activation of macrophages due to alterations in the glycan profile of chondrocytes provides a possible explanation for the antigenicity and immune rejection of transplanted cells.